Graphene-Based Absorption–Transmission Multi-Functional Tunable THz Metamaterials - Shulei Zhuang; Xinyu Li; Tong Yang; Lu Sun; Olga Kosareva; Cheng Gong; Weiwei Liu (Micromachines, 2022)
The paper reports an absorption–transmission multifunctional tunable metamaterial based on graphene. Its pattern graphene layer can achieve broadband absorption, while the frequency selective layer can achieve the transmission of specific band. Furthermore, the absorption and transmission can be controlled by applying voltage to regulate the chemical potential of graphene. The analysis results show that the absorption of the metamaterial is adjustable from 22% to 99% in the 0.72 THz~1.26 THz band and the transmittance is adjustable from 80% to 95% in 2.35 THz. The metamaterial uses UV glue as the dielectric layer and PET (polyethylene terephthalate) as the flexible substrate, which has good flexibility. Moreover, the metamaterial is insensitive to incident angle and polarization angle, which is beneficial to achieve excellent conformal properties.